Effect of Quizz Learning Media on Students' Learning Outcomes - Yulan, Yulan; Herlina, Herlina; Idrus, Idrus (Journal of Education Method and Learning Strategy, 2025)
Technology influences how the education process will be given and how students learn and prepare themselves for a bright future.​ Technology is expected to solve many problems. This is faced in the education world in Indonesia. Formulation problem study whether There is an influence use of learning media quiz to results Study participant educate on the eyes science lessons (science) Natural and Social Sciences) in class IV MI Al-Khairat Sakita. The Study aims to determine the influence of a learning media quiz on the results of the eyes science lessons (science) Natural and Social Sciences) class IV at MI Al-Khairat Sakita. The type of research used is a quantitative study. “ Research quantitative is research that produces new findings that can be achieved (obtained) by using procedures in a way statistics or method other than a quantification/measurement. Research results The significance level used is 0.05, where if the sig value < 0.05, then the question instrument is said to be valid. Table Validity test results are served using SPSS. Research conclusions Based on the analysis results Study, there is a significant influence of learning media quizzes on the results students learn science Class IV MI Al-Khairat Obata District. Bungku Tengah District. Morowali Central Sulawesi Province.